"Priče iz davnine: hrvatska historiografska metafikcija?" - Jukić, Tatjana (Array, 2003)
The paper explores various effects of the dominant, mostly Anglo-American theorizing of historiographic metaficton, when applied to the body of contemporary Croatian historical novels (Pavličić, Fabrio, Tomaš, Aralica...). In view of the exigent focus of these narratives on the figures of cultural and historical others, the author proposes a more manifest transdisciplinary fusion of the existing conjectures about historiographic metafiction (based primarily on metahistory) with anthropology and psychoanalysis.